Umbilical cord derived mesenchymal stromal cells in microcarrier based industrial scale culture sustain the immune regulatory functions. Issue 6 (14th April 2021) - Kurogi, Hikari; Takahashi, Atsuko; Isogai, Maya; Sakumoto, Marimu; Takijiri, Takashi; Hori, Akiko; Furuno, Tetsuo; Koike, Tetsuo; Yamada, Tetsumasa; Nagamura‐Inoue, Tokiko; Sakaki‐Yumoto, Masayo
Abstract: Mesenchymal stromal cells (MSCs) have been isolated from numerous sources and are potentially therapeutic against various diseases. Umbilical cord‐derived MSCs (UC‐MSCs) are considered superior to other tissue‐derived MSCs since they have a higher proliferation rate and can be procured using less invasive surgical procedures. However, it has been recently reported that 2D culture systems, using conventional cell culture flasks, limit the mass production of MSCs for cell therapy. Therefore, the development of alternative technologies, including microcarrier‐based cell culture in bioreactors, is required for the large‐scale production and industrialization of MSC therapy. In this study, we aimed to optimize the culture conditions for UC‐MSCs by using a good manufacturing practice (GMP)‐compatible serum‐free medium, developed in‐house, and a small‐scale (30 mL) bioreactor, which was later scaled up to 500 mL. UC‐MSCs cultured in microcarrier‐based bioreactors (MC‐UC‐MSCs) showed characteristics equivalent to those cultured statically in conventional cell culture flasks (ST‐UC‐MSCs), fulfilling the minimum International Society for Cellular Therapy criteria for MSCs. Additionally, we report, for the first time, the equivalent therapeutic effect of MC‐UC‐MSCs and ST‐UC‐MSCs in immunodeficient mice (graft‐versus‐host disease model). Lastly, we developed a semi‐automated cell dispensing system, without bag‐to‐bag variation in the filled volume or cell concentration. In summary, our results show that the combination of our GMP‐compatible serum‐free and microcarrier‐based culture systems is suitable for the mass production of MSCs at an industrial scale. Further improvements in this microcarrier‐based cell culture system can contribute to lowering the cost of therapy and satisfying several unmet medical needs. Abstract : Mesenchymal stromal cells (MSCs) are potentially therapeutic against various diseases. In this study, the authors demonstrate microcarrier‐based culture systems are capable of maintaining stable proliferation and ISCT criteria in umbilical cord MSCs (UC‐MSCs), as well as its immune modulatory effects both in vitro and in vivo. Further, the authors developed novel semi‐automated system to dispense and cryopreserve the cells produced. This work is the potential basis for manufacturing MSC products at industrial scale, contributing to lowering costs and satisfying unmet medical needs.